Development Of A Gis Based Peat Swamp Forest Fire Hazard Model - Setiawan, Iwan (2007)

(untitled)
A GIS-Based peat swamp forest fire hazard model that integrated AHP process and GIS analysis was developed. A GIS-grid based fire vulnerability map was thus produced for Pekan, Pahang. High correlations (100%) were observed between fire vulnerability zone map that derived from the model with the hotspot distribution locations processed from NOAA satellite data in August 2002 and actual fire spot location recorded by Pahang State Forestry Department in 1997. The model was tested for fire vulnerability zone using recorded actual fire spot location and NOAA hotspot locations where all of the fire spots locations whether from Pahang State Forestry Department or NOAA hotspots data are located in high and very high vulnerability zone that extracted from the model. The accuracies of maps that derived from the model were verified using hotspot location data extracted from NOAA satellite published by MACRES in August 2002 and actual fire spot locations published by Pahang State Forestry Department. The verification results showed an accuracy of 100%. Arc View Dialog Designer to design Arc View Graphical User Interfaces is used for the development of a software tool to run the model in GIS environment. Extensive Avenue programming scripts were written to provide additional capabilities in the development of these interfaces to meet the full complement of operational software considering various user requirements. The software developed not only have user friendly step by step operations to deliver the fire vulnerability mapping but also allows authorized users to edit, add or modify parameters whenever necessary.